Metode Pendidikan Agama Islam Sekolah Dasar - Ayatullah Ayatullah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2018)
Through the innovative method of Islamic education learning, the learning atmosphere in the classroom is not stuck in a rigid and monotonous atmosphere. So that students will more easily understand the material delivered. Susana learning will make students unsaturated to receive material from teachers. This research uses descriptive qualitative approach. To obtain valid and accurate data, the author uses three data collection techniques. One tool of Islamic education in elementary school is the method of Islamic religious education, which by using the right method then the teachings of religion can be absorbed by students with the best. The right method will determine the effectiveness and efficiency of learning. The meaning in Islam itself has also been taught about the method of teaching, because the Islamic religion is actually not just a system of theology alone, but it is a complete civilization.